THE EFFECTIVENESS OF APPLICATION OF Ventury Air System (VAS) ON MAINTENANCE OF STAR POMFRET FISH (Trachinotus blochii) - Muhamad Latiful Khobir; Syafriadiman Syafriadiman; Henni Syawal (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This research was conducted from 15 March to 15 April 2021Brackishwater Fish Seed center (BBIAP) Kab. Meranti Islands, Riau Province. The stocking density and diameter of the PVC hole had a significant effect onthe growth of the Star Pomfret Fish (Tracinotus blochii). The small diameter ofthe PVC hole will produce air bubbles that burst faster than the diameter of themedium and large PVC hole. In this study, the highest number of bubbles wasproduced in treatment D1 (Ø 2 mm), and the best treatment and the effect onabsolute weight growth of this star pomfret fish was treatment D2 (Ø 3 mm),which was 2,3200 grams. This treatment has an impact on the agile movementand response of the fish to get the food given is very good, as well as the effectof low and high levels of dissolved oxygen resulting from differences in thediameter of the PVC holes. Star Pomfret Fish maintenance can be carried out with a high stockingdensity of up to 500 fish/m3. Where with a diameter of 3 mm PVC hole is ableto provide an absolute weight growth rate of 2,3200 grams, feed efficiency of64.4400%, specific growth rate of 6.0617% and survival rate of 97.51%.